NaF/RbF-Treated Cu(In,Ga)Se2 Thin-Film Solar Cell Absorbers: Distinct Surface Modifications Caused by Two Different Types of Rubidium Chemistry - Bombsch, Jakob; Avancini, Enrico; Carron, Romain; Handick, Evelyn; Garcia-Diez, Raul; Hartmann, Claudia; Félix, Roberto; Ueda, Shigenori; Wilks, Regan G.; Bär, Marcus (ACS Applied Materials and Interfaces, 2020)
The underlying beneficial mechanism of heavy alkali postdeposition treatment (PDT) of Cu(In,Ga)Se2 thin-film solar cell absorbers that led to new record efficiencies in recent years is studied using photoelectron spectroscopy. Excitation energies between 40.8 eV and 6 keV were used to examine the near-surface region of Cu(In,Ga)Se2 thin-film solar cell absorbers that underwent NaF and combined NaF/RbF PDT. The already Cu-deficient surface region after NaF PDT, which is modeled as a Cu:(In + Ga):Se = 1:5:8 phase, shows further depletion after NaF/RbF PDT and seems to incorporate some Rb. Additionally, we have found strong indications for the NaF/RbF PDT-induced formation of a Rb-In-Se-type compound with a 1:1:2 stoichiometry partially covering the absorber surface. The electronic Cu(In,Ga)Se2 structure is modified due to the RbF treatment, with a pronounced shift in the valence band maximum away from the Fermi level in the immediate vicinity of the surface.
CRIS-Team Scopus Importer:2020-08-28
Keywords: chalcopyrites; HAXPES; RbF-PDT; RbInSe2; thin-film solar cells